2016
DOI: 10.1177/1934578x1601101215
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Target of Nobiletin's Action

Abstract: Nobiletin is an O-methylated flavonoid found in citrus peels that have anticancer, antiviral, neuroprotective, anti-inflammatory activities and depending on the cell types exhibits both pro-or anti-apoptotic properties. We have found that nobiletin decreases oxygen consumption by bovine brain isolated mitochondria in the presence of glutamate and malate and increases in the presence of succinate. In parallel, nobiletin increases NADH oxidation, a-ketoglutarate dehydrogenase activities and through matrix substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Several studies have demonstrated that NOB plays an important role in modulating mitochondrial function, including influencing the mitochondrial membrane potential [ 20 , 21 , 22 , 23 ]. To explore whether NOB can improve the mitochondrial function in activated astrocytes induced by hypoxia, we detected the mitochondrial membrane potential using a JC-1 Assay Kit.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that NOB plays an important role in modulating mitochondrial function, including influencing the mitochondrial membrane potential [ 20 , 21 , 22 , 23 ]. To explore whether NOB can improve the mitochondrial function in activated astrocytes induced by hypoxia, we detected the mitochondrial membrane potential using a JC-1 Assay Kit.…”
Section: Resultsmentioning
confidence: 99%
“…Li and coauthors demonstrated that caffeic acid inhibits both JAK/STAT and ERK1/2 pathways, as well as cell proliferation [ 71 ]. Moreover, it was shown that nobiletin, a methylated flavonoid found in citrus peels, suppresses the proliferation of C6 rat glioma cells by inhibiting RAS activity and subsequently reducing MEK/ERK signalling [ 72 ]. The ERK1/2 expression levels did not change significantly following any treatment, while the p-ERK2/ERK2 ratio decreased after pre-treatment with coffee phenolic metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Catechin also inhibits complex I in isolated rat heart mitochondria and decreases H 2 O 2 generation [137]. Nobiletin decreases mitochondrial oxygen consumption and H 2 O 2 production in the presence of glutamate and malate, but a slight increase has been observed with succinate [138]. However, other reports have shown that the inhibition of complex I by an apple peel polyphenol extract leads to increased mitochondrial superoxide production [139].…”
Section: Flavonoids Attenuate Mitochondrial Ros Formationmentioning
confidence: 95%